FINANCIAL RELATIONS AMONG TIERS OF GOVERNMENT IN NIGERIA: AN OVERVIEW - Ibrahim, S. Y.; Adamu, Umar (International Journal of Research -GRANTHAALAYAH, 2017)
The paper reviewed the nature of financial relations among the three tiers of government in Nigeria. It was identified that revenue allocation in every federation is a problem; as such each federation adopts its own strategies to contain the imbalance. It was discovered that several attempts were made, yet the problem still persists. This is because most federating units depend largely on the federal Account. Among the recommendations were review of the relevant sectoring of the constitution and creation of units of government should be based on viability rather than political consideration.